Metal-free radical trifluoromethylation of beta-nitroalkenes through visible-light photoredox catalysis - Midya, Siba P.; Rana, Jagannath; Abraham, Thomas; Aswin, Bhaskaran; Balaraman, Ekambaram (Chemical Communications, 2017)
A catalytic method for functional group interconversion is immensely important in modern sciences. Here, we report an efficient catalytic conversion of nitroalkenes to highly stereoselective 1-trifluoromethylalkenes at room temperature. This unprecedented metal-free photocatalytic strategy is simple and operates under visible-light irradiation using the commercially available CF3 source.